Desentralisasi dan Kinerja Usaha Mikro, Kecil dan Menengah (UMKM) di Jawa Timur - Faridatul Masruroh (Jurnal Administrasi Publik, 2015)
Abstract: Decentralization and Performance of Micro, Small and Medium Enterprises (SMEs) in East Java. Fiscal decentralization has become an important development agenda to develop economy in many developing countries, including Indonesia. This research examines the link between fiscal decentralization and performance of SMEs development in East Java Province 2012. Bivariate correlation analysis is used to test the hypothesis that fiscal decentralization relates to SMEs performance. The population in this study is all districts in East Java which consists of 29 kabupaten and 9 kota. The findings show that the performance of SMEs in East Java is relatively good as can be seen from the high number of SMEs, SMEs employment and high contribution of SMEs on District Gross Domestic Product. Results of bivariate correlation analysis show that the DAU significantly associated with the three measures of performance of SMEs. DAK is significantly related to the amount of SMEs and SME employment. Meanwhile, district budget on SMEs and cooperative are significantly associated on the contribution of the SMEs sector on District Gross Domestic Product. Â  Keywords: Fiscal Decentralization, Micro, Small and Medium Enterprises (SMEs), and East Java Province Abstrak: Desentralisasi dan Kinerja Usaha Mikro, Kecil dan Menengah (UMKM) di Jawa Timur. Desentralisasi fiskal telah menjadi agenda penting bagi pembangunan ekonomi di Negara-negara berkembang termasuk Indonesia. Penelitian ini bertujuan untuk menganalisis hubungan desentralisasi fiskal dan kinerja UMKM di Jawa Timur tahun 2012. Analisis korelasi digunakan untuk menguji hipotesis apakah desentralisasi fiskal berhubungan dengan kinerja UMKM di Jawa Timur. Populasi dalam penelitian ini adalah seluruh kabupaten/kota Propinsi Jawa Timur, terdiri dari 29 kabupaten dan 9 kota. Hasil penelitian menunjukkan bahwa kinerja UMKM di Jawa Timur setelah hampir 15 tahun desentralisasi dapat dikatakan relatif baik. Hal ini ditunjukkan dari jumlah UMKM, penyerapan tenaga kerja UMKM, dan kontribusi PDRB UMKM yang relatif besar pada perekonomian Jawa Timur. Berdasarkan analisis korelasi ditemukan bahwa DAU berhubungan dengan ketiga ukuran kinerja UMKM. DAK berhubungan dengan jumlah UMKM dan penyerapan tenaga kerja UMKM. Sedangkan, besarnya dana koperasi UMKM dan PAD berhubungan dengan besarnya kontribusi PDRB sektor UMKM di Jawa Timur. Â  Kata kunci: Desentralisasi Fiskal, Kinerja Usaha Mikro, Kecil, dan Menengah (UMKM), dan Provinsi Jawa Timur.